Gerakan literasi masyarakat berbasis media sosial - Johan, Riche Cynthia; Emi Emilia; Syahid, Aah Ahmad; Hadiapurwa, Angga; Rullyana, Gema (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. The three main aspects to improve literacy movement are family, school, and society. Using social media could be useful to improve literacy as many reading materials can be accessed and freely available. However, the content should be selected to prevent from unexpected materials. Data Collection Method. Data obtained through observations of 100 participants in the development of community literacy movement. They were religious education community (pesantren) with professions such as, teachers, education staffs and students’ representatives from two levels of education within the reading village frameworks in Tanjungmekar village, Tanjungkerta, Sumedang. Analysis Data. Data were analyzed using descriptive percentage studies, and describing the results of observations. Result and Discussions. The community accesses reading material dominant using printed material, reading assignment and communication through social media have not done as expected. In general, the activities of fostering literacy in the religious education community require patterns that are in accordance with time, motivation, access, technological devices, various social media to foster literacy readiness. Conclusions. Alternative use of social media is expected be able to support community movement to build the literate village.